Analysis of the Application of CIA Triad Information Security Aspects in Academic Information Systems - Hidayasari, Nurmi; Kasmawi, Kasmawi; Mansur, Mansur; Husaini, M. Iqbal; Nuranisa, Putri (ABEC Indonesia, 2024)
Threats that often attack information systems such as data leakage, credentials (account compromise),phishing, web-based attacks, malware attacks, cracking (piracy), carding (illegal transactions) and so on. These types ofcrimes can certainly be prevented and handled which is the responsibility of the company/organization. Informationsecurity is an effort to protect information assets from potential threats. Information security indirectly ensures businesscontinuity, reduces emerging risks, and makes it possible to optimize return on investment. The CIA Triad InformationSecurity aspect in information and data systems is very important as a guideline or basic framework, because in it thereare indicators in preventing Cyber Crime. Politeknik Negeri Bengkalis (Polbeng) as one of the State VocationalUniversities in Indonesia already uses SIAKADCloud, a SEVIMA product as an integrated academic managementinformation system. In addition, SEVIMA also claims that SIAKADCloud is a secure system. However, so far it has notbeen possible to ascertain the extent of its security. It is also necessary to know whether in its implementationSiakadCloud has implemented basic security standards in accordance with the CIA Triad, namely Confidentiality,Integrity, and Availability. To find out the application of Confidentiality do Block Direct, To find out the application ofIntegrity do User and Data filtering checks: user level division, while to find out the application of Availability doauthentication.